Motion training on a validated mechanical ERCP simulator improves novice endoscopist performance of selective cannulation: a multicenter trial - Voiosu, Theodor; Puscasu, Claudia; Orlandini, Beatrice; Cavlina, Masa; Bekkali, Noor; Eusebi, Leonardo Henry; Pizzicannella, Margherita; Blero, Daniel; Balanescu, Paul; Voiosu, Andrei; Perretta, Silvana; Rustemovic, Nadan; Fuccio, Lorenzo; Mateescu, Radu Bogdan; Hassan, Cesare; Wani, Sachin; Costamagna, Guido; Boskoski, Ivo (Endoscopy International Open, 2021)
Background and study aims Current data show that traditional training methods in endoscopic retrograde cholangiopancreatography (ERCP) fall short of producing competent trainees. We aimed to evaluate whether a novel approach to simulator-based training might improve the learning curve for novice endoscopists training in ERCP.Methods We conducted a multicenter, randomized controlled trial using a validated mechanical simulator (the Boškoski-Costamagna trainer). Trainees with no experience in ERCP received either standard cannulation training or motion training before undergoing standard cannulation training on the mechanical simulator. Trainees were timed and graded on their performance in selective cannulation of four different papilla configurations.Results Thirty-six trainees (16 in the motion training group, 20 in the standard group) performed 720 timed attempts at cannulating the bile duct on the simulator. Successful cannulation was achieved in 698 of 720 attempts (96.9 %), with no significant difference between the two study groups (P = 0.37). Trainees in the motion training group had significantly lower median cannulation times compared to the standard group (36 vs. 48 seconds, P = 0.001) and better technical performance on the first papilla type (P = 0.013). Conclusions Our findings suggest that motion training could be an innovative method aimed at accelerating the learning curve of novice trainees in the early phase of their training. Future studies are needed to establish its role in ERCP training programs.